The Effectiveness of Utilizing Facebook Media on the Home Notification Page to Improve Poetry Writing Ability at Class X SMA NURUL IMAN - Pratiwi, Fadhillah; Harahap, Rosmawati (Al'Adzkiya Journal, 2023)
The research was carried out which aims to describe the use, application, and use of Facebook media on the notification page of the homepage in writing poetry by students of class X SMA Nurul Iman. This study used a quantitative descriptive method with a population of 180 people and a set sample of 27 people. The total selection was 15% of the total population. The highest score obtained was 90 while the lowest score was 75. Based on the results of data analysis, the average score of class X SMA Nurul Iman students was 81.85 (85%) which was categorized as